Immobilized boronic acid for Suzuki-Miyaura coupling: Application to the generation of pharmacologically relevant molecules - Martinez Amezaga, Maitena (2017)
An synthetic strategy for the generation of a variety of biaryl and related derivatives, based on Suzuki-Miyaura coupling using immobilized boronic acid, is described. The importance of the methodology was demonstrated by its further application to biologically interesting compounds such as 4-biaryl-β-lactams, descripted as cholesterol absorption inhibitors and anti-MRSA active agents, neoflavonoids, imidazoles, isoxazolines, among others.